Pengaruh Penerapan Prinsip-Prinsip Good Governance Terhadap Kinerja Pada Rumah Sakit Di Kota Denpasar - Arina Mahadewi, Ida Ayu; Dwija Putri, IGAM Asri (E-Jurnal Akuntansi; Vol 27 No 1 (2019), 2019)
This study aims to determine the effect of the principles of Good Corporate Governance, namely: transparency, accountability, responsibility, independence, and fairness to the performance of hospitals in the city of Denpasar. The number of samples or population used in this study were 20 hospitals with the determination of samples using purposive sampling method, the total number of respondents was 120 respondents. The data analysis technique used is multiple linear regression analysis. Based on the results of this study indicate that transparency, accountability, responsibility, independence, and fairness positively influence the performance of hospitals in the city of Denpasar. The results of this study are expected to be able to provide information for parties involved in measuring performance in hospitals in the city of Denpasar by applying the principles of Good Corporate Governance in making decisions and determining policies in the future so that later can improve organizational performance. Keywords: Transparency, accountability, responsibility, independence, fairness, performance